Respuesta :
Answer:
D
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
here m = - 6 and (a, b) = (- 9, - 3), so
y - (- 3) = - 6(x - (- 9)), that is
y + 3 = - 6(x + 9)
Answer:
y+3=-6(x +9)
Step-by-step explanation:
equation represents a line that passes through (-9, -3) and has a slope of -6is:
y+3=-6(x +9)
because : The equation of a linear function in point-slope form is: y – y1 = m(x – x1) ....m : the slope
The point is A (x1 , y1)
you have m = - 6 x1 = -9 y1 = -3